1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Taking x = 4, find the values of the following algebraic expressions. (1) 5 − x (2) 3 (5 − x) (3) (5 − x)2 (4) (x + 2)2 (5) 3(x + 2) (6) 2 (x + 2) + 3

Open in App
Solution

## (1) 5 − x Substituting the value of x in the given expression, we get: 5 − 4 = 1 (2) 3 (5 − x) Substituting the value of x in the given expression, we get: 3(5 − 4) = 3 × 1 = 3 (3) (5 − x)2 Substituting the value of x in the given expression, we get: (5 − 4)2 = (1)2 = 1 (4) (x + 2)2 Substituting the value of x in the given expression, we get: (4 + 2)2 = (6)2 = 36 (5) 3( x + 2) Substituting the value of x in the given expression, we get: 3(4 + 2) = 3 (6) = 3 × 6 = 18 (6) 2 (x + 2) + 3 Substituting the value of x in the given expression, we get: 2 (4 + 2) + 3 = 2 × 6 + 3 (Solving addition in the simple brackets first) = 12 + 3 (Performing multiplication first) = 15

Suggest Corrections
0
Join BYJU'S Learning Program
Related Videos
Word Problems
MATHEMATICS
Watch in App
Join BYJU'S Learning Program